Comparison of 1800MHz Frequency Bands Path Loss Measurements with Conventional Models in Osun State, Nigeria - Abiodun, Isaac Chukwutem; Ukhurebor*, Kingsley Eghonghon (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2021)
The role of propagation models in the planning of wireless network, evaluation of cell parameters and frequency assignment cannot be overemphasized. One of the major difficulties with the application of path loss predicting models for any environment is that no two environments are the same in building patterns, terrain, atmospheric conditions, etc. It is therefore impracticable to formulate a single path loss model for all environments. In this study, an assessment of microwave frequency band measurement results based on received signal strength (RSS) values from four base stations in four urban environments in Osun State, Nigeria, are presented. The measured path loss values of each base station were extracted from the RSS values and compared with the results estimated from five conventional path loss models. Model comparison results based on three metric measures and fitting accuracy showed that a log-normal shadowing model exhibited a better agreement with the measured path loss with RMSE of less than 8 dB, the lowest RE, and R2 closer to one, in all the environments monitored. The best probable probability distribution for modelling the path loss at the investigated urban environments was also determined. The result of the various distribution functions tested using three goodness of fits showed that the normal distribution function offered the best match with the path loss values based on RMSE, RE, and R2 values calculated and fitting accuracy for both environments. Practical path loss parameters were also estimated for each of the base stations considered. The overall results should be useful for planning future mobile network channels. Keywords: received signal strength; path loss; path loss models; probability distribution functions; wireless network *Corresponding author: Tel.: +2348035383194 E-mail: ukhurebor.kingsley@edouniversity.edu.ng